Eating the inedible: cues of caco-gastro-maniac semiotics - Marino, Gabriele (E|C, 2020)
This work investigates the idea of inedible food, yet eaten, and that of such a cacogastromania, the overturning of the gastromania studied for so long and in depth by Gianfranco Marrone - the aesthetic obsession with food, cooking and their discursive. Some examples of “anti-food” (unedited, impossible, wrong, forbidden food) are briefly reviewed, commented on and interrelated: the anti-traditionalist recipes of Futurist cuisine; scatophagy, hyperphagia and pica as oppositional identity practices (often connoted in a sub-cultural or counter-cultural sense); various types of post food, including the Soylent "mash", in vitro meat and engineering and experimental creations that seem to chase after the inventions of science fiction (eg the Living Food project). Finally, the case of cucinaremale: a Facebook group dedicated precisely to inedible foods (by definition, because "cucinatimale"), but not without internal forms of self-regulation, up to self-censorship, which define its terms and boundaries of lawfulness.